Wind Tunnel and Numerical Modeling of Atmospheric Boundary Layer Flow Over Bolund Island. (January 2016) - Vladut, Alexandru Cezar; Cosoiu, Costin Ioan; Georgescu, Andrei Mugur; Degeratu, Mircea; Damian, Radu Mircea
Abstract: The paper presents a comparison between the experimental and numerical results on the flow around a Bolund Island 1:705 scale model. A boundary layer wind tunnel with expansion stage was used for experimental modelling[9] . Velocity fields were determined using Constant Temperature Anemometry (CTA) and Particle image Velocimetry (PIV) measurements. Unsteady numerical simulations were performed using a Reynolds Average Navier Stokes (RANS) turbulence model adapted to atmospheric boundary layer flows[6] which was implemented in the ANSYS FLUENT expert software. At the beginning, the wind tunnel with expansion stage was explored and measurements were performed to determine the flow characteristics in the experimental vein. Data from CTA measurements in the median longitudinal plane, in eleven sections located at different distances from the expansion stage were used to determine mean velocity ant turbulence intensity profiles. Comparison with real data from the Bolund experiment showed a good agreement with the wind tunnel measurements. The experimental 1:705 scale model of the Bolund Island was manufactured on a CNC machine using the topographical data provided by the Risø DTU team from the Bolund experiment. Same data was used to build the mesh which virtually replicates the model placed in the experimental vein of the wind tunnel. PIV measurements were performed in order to determine the velocity, turbulence intensity and vorticity contours in a vertical reference plane and then compared to the URANS numerical simulation results.